Synthesis and Characterization of Low Temperature Sintering Alumina Structural Ceramics for Armor Facing - NUGROHO AJIE (NIM 13703011), GALIH
The use of structural ceramics for ballistic protection is a relatively new application. Ceramics offer an advantage over steel in weight reduction. The densities of structural ceramics are typically 2.5 - 4 gr/cm3, while steel are roughly 7.8 gr/cm3. There are two types of hard ceramic materials used for ballistic protection: monolithic structural ceramics and ceramic-matrix composites. This research purposed to production and characterization structural alumina ceramics which have low temperature sintering both monolithic structural ceramic and ceramic matrix composite. In structural alumina ceramics type CMC, alumina is used as matrix and zirconia as reinforcement in form of particulate. Production process used here is dry pressing with activated solid state sintering, which is sintering process by adding additive or activator such as niobia, silica, and magnesia. the mechanical and physical properties testing used is hardness, fracture toughness, modulus of elasticity, and specific mass determination. Micro structure characterization is done using SEM, EDS, and XRD. Mechanical properties resulted from hardness testing showed a satisfying value. hardness value gained from 8 low-sintered samples have the value that had been determined by previous research. the highest value reached by using the composition with additive on alumina matrix as much as 4%wt niobia + 0.8%wt silica + 0.5%wt magnesia + 15%wt zirconia with hardness value of 1432+28 Kgf/mm2, modulus of elasticity 331 + 11 GPa, and specific mass 3.98 gr/cm3.